Creep characteristics of muddy submarine channel slope instability - Zhang, Cunyong; Hou, Jiankang (Frontiers in Marine Science, 2022)
Creep is an important factor of muddy submarine channel slope instability. In this study, a sub-bottom profiler was used to monitor the continuous internal change of a muddy submarine channel slope in the laboratory to better understand the creep characteristics and mechanism of slope instability. The creep process was analyzed according to changes in the slope internal sound intensity. The results indicate a notable change of the creep characteristics during the slope instability process. Changes in the sound intensity time series decrease with increasing slope depth, and the fluctuation depth of the vertical sound intensity series varies during the slope creep process. The creep process of slope instability can be roughly divided into four stages based on the sub-bottom profile data: an expansion stage; an unstable expansion stage; a fracture stage; and a post-fracture development stage. An adjustment of the sediment microstructure in the slope is ascribed to slope creep deformation. This study highlights the prospects of high-resolution acoustic monitoring to detect and quantify the entire creep process of muddy submarine channel slope instability, which is of great significance for the evaluation and early warning prediction of channel slope instability.